Can pocket parks be compared to community parks in the restoration effect of physical and mental health for young adults? A comparative experiment in high-density urban Green spaces - Zhang, Yuzhe; Hu, Yunhong; Wei, Yunqi; Xie, Yuge (Frontiers in Public Health, 2025)
IntroductionUrban intensification limits the availability of green space, leading to the rise of pocket parks as a strategy approach to urban greening. Unlike conventional community parks, pocket parks are smaller in scale and function, necessitating further investigation into their capacity to support psychophysiological restoration. Specifically, understanding which landscape elements within pocket parks most effectively facilitate recovery in young adults is essential to determining whether these spaces can achieve restorative outcomes comparable to those of larger community parks.MethodsThis study examines the restorative efficacy of pocket parks by comparing two pocket parks and two community parks in Nanjing, each representing distinct typologies—one prioritizing vegetation and the other prioritizing artificial environments, including hardscape activity zones. Eighty participants (aged 18–28) were randomly assigned to different park types, where their psychological and physiological responses were assessed using standardized surveys and biometric measurements.ResultsThe findings indicate that, despite their smaller size, well-designed pocket parks with diverse landscape features significantly enhance users’ psychological relaxation and emotional well-being, achieving restorative effects comparable to those of community parks. Notably, this research highlights the critical role of hardscape activity areas in promoting restoration among young adults, an overlooked aspect of park design.DiscussionThese results underscore the imperative of prioritizing “quality” in park design and renovations, advocating for integrating diverse landscape elements within limited spaces to optimize holistic recovery in urban environments.